c) y+z+1 /x=x+z+2/y=x+y-3/z=1/x+y+z
Đề là thế này này:
[TEX]\frac{y+z+1}{x}[/TEX]=[TEX]\frac{x+z+2}{y}[/TEX]=[TEX]\frac{x+y-3}{z}[/TEX]=[TEX]\frac{1}{x+y+z}[/TEX]
Vì [TEX]\frac{y+z+1}{x}[/TEX]=[TEX]\frac{x+z+2}{y}[/TEX]=[TEX]\frac{x+y-3}{z}[/TEX]
\Rightarrow [TEX]\frac{x+y+z+x+y+z+0}{x+y+z}[/TEX]
Vì x+y+z khác 0
\Rightarrow [TEX]\frac{1}{x+y+z}[/TEX]=2
Suy ra x+y+z=0,5
Thay vào ta được:
[TEX]\frac{0,5-x+1}{x}[/TEX]=2
\Rightarrow x=[TEX]\frac{1,5}{3}[/TEX]
[TEX]\frac{0,5-y+2}{y}[/TEX]=2
\Rightarrow y=[TEX]\frac{2,5}{3}[/TEX]
[TEX]\frac{0,5-z-3}{z}[/TEX]
\Rightarrow z=[TEX]\frac{-2,5}{3}[/TEX]